Modelling the control strategies for riding a motorcycle - Rowell, Stuart (2007)
Computer simulation models are increasingly necessary as a design tool for modern vehicles, for which a subcategory relates to motorcycles. Simulation models can be employed for a variety of applications, an important area of which relates to the motorcycle's dynamic responses. The response of a motorcycle is heavily dependent on the rider's control actions, and consequently a means of replicating the rider's actions provides an important extension to this area.